1) -5(3a+1)-11=-16
-15a-5-11=-16
-15a-16=-16
-15a=0
a=0
2) -3,2n+4,8=-2*(1,2n+2,4)
-3,2n+4,8=-2,4n-4,8
-3,2n+2,4n=-4,8-4,8
=-0,8n=-9,6
n=12
3) -5*(0,8z-1,2)=-z+7,2
-4z+6=-z+7,2
-4z+z=7,2-6
-3z=1,2
z=-0,4
1)-5*(3a+1)-11=-16
-15a=-16+5+11
a=0/(-15)
2)-3,2n+4,8=-2*(1,2n+2,4)
-0,8n=-9,6
n=-9,6/(-0,8)
3)-5*(0,8z-1,2)=-z+7,2
z=1,2/(-3)
1) -5(3a+1)-11=-16
-15a-5-11=-16
-15a-16=-16
-15a=0
a=0
2) -3,2n+4,8=-2*(1,2n+2,4)
-3,2n+4,8=-2,4n-4,8
-3,2n+2,4n=-4,8-4,8
=-0,8n=-9,6
n=12
3) -5*(0,8z-1,2)=-z+7,2
-4z+6=-z+7,2
-4z+z=7,2-6
-3z=1,2
z=-0,4
1)-5*(3a+1)-11=-16
-15a-5-11=-16
-15a=-16+5+11
a=0/(-15)
a=0
2)-3,2n+4,8=-2*(1,2n+2,4)
-3,2n+4,8=-2,4n-4,8
-3,2n+2,4n=-4,8-4,8
-0,8n=-9,6
n=-9,6/(-0,8)
n=12
3)-5*(0,8z-1,2)=-z+7,2
-4z+6=-z+7,2
-4z+z=7,2-6
-3z=1,2
z=1,2/(-3)
z=-0,4